Atlas : the archaeology of an imaginary city - Dong, Qizhang, 1967- (Weatherhead books on Asia., 2012)
Set in the long-lost City of Victoria (a fictional world similar to Hong Kong), this book is written from the unified perspective of future archaeologists struggling to rebuild a thrilling metropolis. It reimagines Victoria through maps and other historical documents and artifacts, mixing real-world scenarios with purely imaginary people and events while incorporating anecdotes and actual and fictional social commentary and critique.--From book jacket.